PENINGKATAN KUALITAS HIDUP PASIEN KANKER RUMAH SINGGAH MELALUI PENDAMPINGAN KELUARGA PASIEN DI YAYASAN KANKER INDONESIA (YKI) CABANG JAWA TIMUR - Fajariah, Isnaini; Fatmawati, Desy; Wahyuningtyas, Ellen; Reza, Chaerul (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Indonesian Cancer Foundation (YKI) is a nonprofit organization that has the sole purpose of social and humanitarian field, especially in the fight against cancer that already have networks across the province in Indonesia. Halfway house is a place reserved for cancer patients who are undergoing outpatient care to facilitate the patient to reach the hospital patients who were referred for treatment. With the alternative activities that are beneficial to patients and their families, we propose a program